Preemptive Patenting and the Persistence of Monopoly: Reply - Gilbert, Richard J.; Newbery, David (American Economic Review, 2016)
Stephen Salant takes issue with a single paragraph of our 1982 paper (Section IIC, p. 518) and then claims that our conclusions result either from faulty logic or from our implicit assumption that a market fails to operate. We respond by showing that our conclusions are logically consistent, and that Salant's argument is flawed by its incompleteness. The preemptive patenting results hold whenever equally efficient firms compete with nonzero transaction costs (a point which is not contested by Salant), and whenever any cost disadvantage experienced by the incumbent is less than the transaction costs incurred in the process of bargaining for production rights. Furthermore, we will show that if the incumbent's cost disadvantage exceeds transaction costs, then the preemption result hinges on the relative transaction costs in the markets for R&D outputs and inputs. The conditions derived by Salant are erroneous, and indeed irrelevant to the incentives for preemption. Salant mounts his main argument on the assumption that transaction costs are zero, but fails to realize the full implications of this counterfactual assumption. Ronald Coase told us many years ago that bargaining in the absence of transaction costs (broadly interpreted) will eliminate cost inefficiencies and yield a Pareto optimal allocation. By selecting excerpts from two different papers and then providing his own emphasis, Salant constructs the impression that our results contradict the Coase argument. We feel this creative journalism is an inaccurate representation of our conclusions. The implications for preemptive patenting depend on transaction costs, as Salant shows. For any finite transaction cost, an equally efficient monopolist can preempt competitors (subject to the technological and strategic assumptions in our model). Salant argues that if a monopolist is less efficient than a rival, and if the cost penalty exceeds transaction costs, then the rival firm will preempt the monopolist. As it stands, this conclusion is false. It is arbitrary to restrict bargaining, as Salant does, to a single market or group of markets. If firms can negotiate in the patent market, they can also negotiate in markets for inputs to the R&D process. Assuming (as we had explicitly done) no diseconomies that are solely due to management, technological inefficiency must be the result of inferior R&D inputs. These inputs can be bargained for as well.